REVALORIZACIÓN DE PROPIEDADES PLANTA Y EQUIPO (PPYE) UNA APLICACIÓN DESDE ECUADOR - Chávez Cruz, Gonzalo Junior (2017)
This article discusses the importance of the application of IFRS (International Financial Reporting Standards) in Ecuador using the group of accounts called: Property, Plant and Equipment (PP&E) revaluation. To do this, we analyze conceptually how financial statements should be reported and recorded at fair value, considering some countries in the world where there is significant progress in this area, we review models and revaluation techniques that allow us to understand technical procedures. Methodologically, we used information from a local transport company, which allowed us to create a chart of accounts to recording and accounting the revaluation of buildings, in addition, this is exemplified using a process chart and explanatory tables of how to make the adjustment using the regulations of the IFRS. The results show that the value of buildings in the company’s financial statements is not being properly recorded by not using IFRS 16, which is the guide for the correct use of a revaluation of an account belonging to Property, Plant and Equipment. Finally, the importance of properly advising the managers of companies on this type of revaluation is considered, due to the existing financial and tax implications.